Self-deception in forensic self-reports: Detection, effects and testing the model - Arce, Ramón; Fariña, Francisca; Sanmarco, Jéssica; Novo, Mercedes (Anales de Psicología / Annals of Psychology, 2025)
Background/aims: Dissimulation, understood as a positive self-presentation in self-reports, is suspected in child custody dispute forensic evaluations. Dissimulation is displayed through two-manifestations: concealment of negative qualities (denial of symptoms) and claiming non-existent positive qualities or exaggerating existing ones (social desirability). Moreover, the nature of dissimulation may be conscious (impression management) or unconscious (self-deception). Nevertheless, the effects of self-deception in self-reports of parents involved child custody forensic disputes are unknown. Thus, a field study was designed with the aim of determining the efficacy of self-deception measures, the effects of dissimulation on self-reported mental health markers, and to test the purportedly unconscious nature of self-deception. Method: 223 parents involved in court-mandated child custody proceedings endorsed the MMPI-2 and 100 parents from intact families under standard instructions. The K, S, Esd and PMH4 measures of self-deception, the standard clinical scales and the obvious and subtle subscales were scored. Results: The results exhibited significant higher scores, consistent with dissimulation, were observed in the population suspected of dissimulation (child custody litigants) in K, S, and Esd scales; and a significant association between dissimulation classification and dissimulation suspected population. In relation to the effects of dissimulation, the results showed that the suspected population of dissimulation reported significantly fewer clinical symptoms (denial of symptoms) and more positive qualities related to being granted child custody (social desirability). Finally, the results suggested that the underlying process of self-deception is not unconscious for the individual exercising conscious control over his/her biased responses. Discussion: The implications of the results for forensic psychology evaluation of child custody dispute cases and the two-component model for dissimulation are discussed.